Implementasi Continuous Authentication dengan Token pada Wireless Sensor Network (WSN) berbasis LoRaWAN - Regita Yustania Esyaganitha; Adhitya Bhawiyuga; Kasyful Amron (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Wireless sensor network is a part of Internet of Things (IoT) used to sensing an environment, collecting the sensed data, and sending the information to a nearer gateway on the same wireless sensor network environment. Communication between sensor node and gateway needs to be connected to a wireless communication module to finally called a wireless sensor network, one of many technologies that support a wireless connection for wireless sensor network is LoRaWAN. Long-range and low-power feature that provided by LoRa making it the attractive candidate for smart sensing devices that usually used to sense temperature, air pressure, humidity, resonance, and many more according to needs. On a fast-paced moving environment, authentication between device to device is a mandatory issue that needs to be fixed to ease an authentication without enlarge the security gap. This research proposed an idea of lightweight authentication and enhanced security using a dynamic value as example is token that never have the same values for the whole communication session. With the advantage of using token with timeouts, continuous authentication supposed to reduce the possibility of invalid node or intruder node to join the existed communication. The result of this research is, continuous authentication can distinguish the valid node with the invalid one based on their id and the token value that used for authentication. Besides, the system performance with continuous authentication shows 100% success rate on an ideal time and average time needed for sensor node to generate an authentication token is 41,5 ms.